The "patriarchic" state in black Africa : premises, ideology, functioning and evolution of an hybrid state - (:unkn) unknown (My University, 1994)
The state in black Africa is a political project fundamentally different from what has been obtained and what can be seen elsewhere, particularly in the west. Many theories have attempted to explain this form of political organisation in more or less convincing way. In our opinion, the state in black Africa is a "patriarchie", that is, a political system based on the authority and the leadership of a person who is the "founding father" and who holds essential powers and creates filial relationships with the governed. This state is created by an institutional process of hybridation which borrows elements from the local socio-political system; these elements are conjugated with those originating from modes of organisation of foreign societies. In a strategy of carrying out leadership of the "patriarque", the "patriarchic" state creates a monolithic or pluralistic organisation. It ensures the stability of the government. By the ideology of "African authenticity", and also by the political violence and the "patrimonialisation" of the national economy. This type of state is that which we observed in Zaire, Togo, Ivory Coast and Gabon during the last 25 or 30 years.
Keywords: African Research